Sexual function in women with endometriosis and pelvic floor myofascial pain syndrome - Rayanne Moreira da Cunha; Mariana Oliveira Veloso; Samuel Soares Coutinho; Luana Darc de Menezes Braga; Adriana Silva de Barros; Germana Mesquita Magalhães; Pedro Olavo de Paula Lima; Simony Lira do Nascimento; Leonardo Robson Pinheiro Sobreira Bezerra (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To evaluate and compare the sexual function and pelvic floor muscles (PFM) function of women with endometriosis and chronic pelvic pain (CPP) with and without Myofascial Pelvic Pain Syndrome (MPPS). Methods: Cross-sectional study conducted between January 2018 and December 2020. Women with deep endometriosis underwent assessments for trigger points (TP) and PFM function using the PERFECT scale. Electromyographic activity (EMG) and sexual function through Female Sexual Function Index (FSFI) were assessed. Statistical analyses included chi-square and Mann-Whitney tests. Results: There were 46 women. 47% had increased muscle tone and 67% related TP in levator ani muscle (LAM). Weakness in PFM, with P≤2 was noted in 82% and P≥3 in only 17%. Incomplete relaxation of PFM presented in 30%. EMG results were resting 6.0, maximal voluntary isometric contraction (MVIC) 61.9 and Endurance 14.2; FSFI mean total score 24.7. We observed an association between increased muscle tone (P<.001), difficulty in relaxation (P=.019), and lower Endurance on EMG (P=.04) in women with TP in LAM. Participants with TP presented lower total FSFI score (P=.02). TP in the right OIM presented increased muscle tone (P=.01). TP in the left OIM presented lower values to function of PFM by PERFECT (P=.005), and in MVIC (P=.03) on EMG. Conclusion: Trigger points (TP) in pelvic floor muscles (PFM) and obturator internus muscle (OIM) correlates with poorer PFM and sexual function, particularly in left OIM TP cases. Endometriosis and chronic pelvic pain raise muscle tone, weaken muscles, hinder relaxation, elevate resting electrical activity, lower maximum voluntary isometric contraction, and reduce PFM endurance.